2018
DOI: 10.5194/acp-2018-1145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dominant role of emission reduction in PM<sub>2.5</sub> air quality improvement in Beijing during 2013–2017: a model-based decomposition analysis

Abstract: <p><strong>Abstract.</strong> In 2013, China's government published the Air Pollution Prevention and Control Action Plan (APPCAP) with a specific target for Beijing, which aims to reduce annual mean PM<sub>2.5</sub> concentrations in Beijing to 60  m<sup>−3</sup> in 2017. During 2013–2017, the air quality in Beijing was significantly improved following the im… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
5
25
0
Order By: Relevance
“…Second, although changes in PM 2.5 concentration are predominantly affected by the emission of pollutants 12,15,19 , meteorological conditions such as wind also have some influence 19,51,52 . We did not consider the effects of meteorological factors but directly assumed the air quality improvement from 2013 to 2017 is the result of APPCAP.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although changes in PM 2.5 concentration are predominantly affected by the emission of pollutants 12,15,19 , meteorological conditions such as wind also have some influence 19,51,52 . We did not consider the effects of meteorological factors but directly assumed the air quality improvement from 2013 to 2017 is the result of APPCAP.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, year 2016 and 2017 witnessed the most severe surface ozone pollution in record over most Chinese cities. The summertime surface MDA8 ozone levels in 2016-2017 averaged over the major Chinese cities increased by about 20% compared to 2013-2014 (Lu et al, 2018a), despite that the Chinese Action Plan on Air Pollution Prevention and Control implemented in 2013 has significantly reduced anthropogenic emissions of nitrogen oxides (NOx=NO+NO2) and alleviated the winter haze pollution (Cheng et al, 2018;Zheng et al, 2018). Exploring source attribution to surface ozone in China is therefore critical to understand the recent ozone increase and to re-examine the air pollution control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the estimated average PM 2.5 concentration in the study area was 48.04 µg/m 3 during 2016-2018, while the average of the ground-level measurements was 45.09 µg/m 3 , indicating a tight estimation consistency. Almost all regions in the study area exceeded the annual Chinese National Ambient Air Quality Standard (CNAAQS) [66] of 35 µg/m 3 in 2016 and 2017, which resulted in a serious health concern for the YRD. When it comes to 2018, part of the south Zhejiang Province was up to the standard, while the other regions failed to reach the standard but had a decreasing trend.…”
Section: Spatiotemporal Dynamicsmentioning
confidence: 99%
“…These improving trends suggested that series of strict air pollution control policies and measures had indeed taken effect, as these actions included energy conservation, the promotion of cleaner fuels and the optimization of the industrial structure. All of these actions focused on reducing local emissions from human activities [66]. Subsequently, the dynamics of daily exposure PM 2.5 concentrations are illustrated in Fig.…”
Section: Spatiotemporal Dynamicsmentioning
confidence: 99%